The interlink between chrono-nutrition and stunting: current insights and future perspectives - Taslim, Nurpudji Astuti; Farradisya, Salsabila; Gunawan, William Ben; Alfatihah, Aulia; Barus, Ria Irmelin Br; Ratri, Liesty Kurnia; Arnamalia, Astri; Barazani, Hero; Samtiya, Mrinal; Mayulu, Nelly; Kim, Bonglee; Hardinsyah, Hardinsyah; et al. (Frontiers in Nutrition, 2023)
Stunting is the one factor that is responsible for the irretrievable damage to children’s mental and physical health. Stunting imitates chronic undernutrition throughout the most extreme critical stages of growth and development of a child in their early life, and due to that stunted child does not completely develop and are too short for their age. Stunting is mainly linked with brain underdevelopment, along with lifelong damaging consequences, comprising weakened mental and learning capacity, deprived performance in school during childhood, and enhanced risks of nutrition linked to chronic long-lasting ailments, such as diabetes, hypertension, diabesity, and obesity in the future. In this review, the authors mainly summarize the latest studies related to chronic nutrition and how it is related to stunting. Optimal nutrition, particularly during pregnancy and the first 24 months of a child's life, is crucial in preventing stunting. Circadian rhythms play a significant role in maternal and fetal health, affecting outcomes such as premature birth and stunting. Maintaining a balanced diet, avoiding late-night carbohydrate-heavy meals during pregnancy, and promoting breastfeeding align with the body's biological clock, which can benefit newborns in various ways. Providing dedicated spaces for breastfeeding in public places is important to support infant health.